Video-based learning versus traditional lecture-based learning for osteoporosis education: a randomized controlled trial - Pojchong Chotiyarnwong (2020)
© 2020, Springer Nature Switzerland AG. Background: Patient education about osteoporosis is an important component of osteoporosis treatment. Aim: To compare the effectiveness of osteoporosis education between video-based learning and traditional lecture-based learning. Methods: Participants who attended the Outpatient Department of Siriraj Hospital during June 2017 to November 2017 were recruited. Ten-question pre- and post-tests were used to evaluate participant osteoporosis knowledge. After finishing the pre-test, patients were randomized to receive osteoporosis education via either traditional lecture-based or video-based learning for 25 min. After the training, patient questions about the subject matter were answered, and then the post-test was administered. Change in score was compared between groups using non-inferiority test at a non-inferiority margin of − 1. Results: Of 413 participants, 207 and 206 people were allocated to the lecture-based group and the video-based group, respectively. There were no significant differences in baseline characteristics, change in score between pre-test and post-test, or change in score between pre-test and retention test between groups. Non-inferiority test revealed the change in score after video-based learning to be non-inferior to traditional lecture-based learning at a difference of > − 1, α = 0.05 (p < 0.001). Discussion: Video-based osteoporosis education can be used as part of a fracture liaison service to provide essential information about osteoporosis to both patients and caregivers. Video-based education is an efficient and effective tool that will reduce dependency on clinicians to provide lecture-based osteoporosis instruction. Conclusions: Since video- and lecture-based education were found to be equally effective, a standard package for both education techniques should be developed and implemented for all patients.